Beyond Born–Oppenheimer based diabatic surfaces of 1, 3, 5-C6H3F3+ to generate the photoelectron spectra using time-dependent discrete variable representation approach. Issue 4 (10th January 2022) - Mukherjee, Soumya; Ravi, Satyam; Dutta, Joy; Sardar, Subhankar; Adhikari, Satrajit
Abstract : The first-principle based BBO formalism is implemented to generate accurate diabatic PESs of 1, 3, 5-C6 H3 F3 + for "correct" assignment of PE spectra. Abstract : In this article, Beyond Born–Oppenheimer (BBO) treatment is implemented to construct diabatic potential energy surfaces (PESs) of 1, 3, 5-C6 H3 F3 + over a series [eighteen (18)] of two-dimensional (2D) nuclear planes constituted with eleven normal modes ( Q 2, Q 9 x, Q 9 y, Q 13 x, Q 13 y, Q 18 x, Q 18 y, Q 10 x, Q 10 y, Q 12 x and Q 12 y ) to include all possible nonadiabatic interactions among six coupled electronic states (X̃ 2 E′′, , B̃ 2 E′ and ). We had formulated explicit expressions of adiabatic to diabatic transformation (ADT) equations [S. Mukherjee, J. Dutta, B. Mukherjee, S. Sardar and S. Adhikari, J. Chem. Phys., 2019, 150, 064308] for the same system forming six state sub-Hilbert space and at present, these ADT equations are solved by incorporating MRCI level ab initio adiabatic PESs and CP-MCSCF calculated nonadiabatic coupling terms (NACTs) to derive diabatic PESs and couplings. Such single-valued, smooth, symmetric and continuous diabatic surface matrices are utilized to carry out multi-state multi-mode nuclear dynamics with the help of time-dependent discrete variable representation (TDDVR) methodology to compute the photoelectron (PE) spectra of 1, 3, 5-C6 H3 F3 . Our theoretically calculated spectra for X̃ 2 E′′, and states using BBO treatment and TDDVR dynamics show peak by peak correspondence with the experimental results as well as better than the findings of the multi-configuration time-dependent Hartree (MCTDH) method.